Flood Early Warning System with Informational Technology for Reducing Risk of Loss in Sustainability of City - Supani, Ahyar; Agustin, Maria; Andriani, Yuli (International Series on Interdisciplinary Science and Technology, 2019)
Palembang is divided by Musi-river consisting of two parts of city called Hulu and Hilir. it has a height of Musi tide surface about 0.7 m to 2.2 m and average high rainfall 101.48 mm/hrs in a year so that it always happen flood every year. In tackling flood, Palembang goverment has did rehabilition of canals, river dredging, creation of retention ponds, demolition of illegal building on the banks of river and the extension services provided to the public about the cleanliness of the river. In addition in this study, it has been also applied infomational technology to tackle the flood in Palembang as early warning system. The flood early warning system that was built for measuring rainfall and water level, predicting flood condition using fuzzy logic and conveying data containing rainfall, water level and flood condition via short message service to people. In test, it was succesfull measuring water level up to 5 metres and rainfall  up to 380 ml/minutes and more, forecasting the flood conditions namely standby 2, standby 1 and flood. Hence, it was also successfull sending short message service containing rainfall, water level and flood conditions automatically. In addition, the increase of rainfall caused the increase of water level and change of flood condition. Meanwhile, it was based on study that the flood early warning system was the key element of disaster risk reduction. From the results, it can be concluded that flood early warning system resulted on flood for 5.0 m, 320.31-418.33 ml/minutes, S1 for 4.0-5.0 m, 243.33-647.5 ml/minutes, S2 for less than 3.6 m, 414.17 ml/minutes. It succeeded in sending data of rainfall, water level and flood as much as 15 times to community's cellulerphone automatically so that it is reducing risk of loss againts flood and maintaining sustainability of city.